An overlapping window decorrelating multiuser detector for DS-CDMA radio channels. - Xiafeng Wang
A new multiuser detector for direct-sequence code-division multiple-access communication systems is described. The proposed detector divides the received signal stream into a number of overlapping windows and decorrelates them window by window. This scheme is justified by an analysis of the convergence and decay rate of the impulse response. Based on the results, a signal-adapted criterion is developed which enables one to determine the window length according to the near-far situation of a practical system. A performance analysis and simulation results show that a small to moderate window length is usually sufficient to yield a performance that is close to or even better than that of the ideal decorrelating detector
Keywords: AWGN channel; DS-CDMA communication systems; DS-CDMA radio channels; IIR filter; QPSK; Convergence; Decay rate; Direct-sequence code-division multiple-access.; Ideal decorrelating detector; Impulse response; Near-far situation; Overlapping window decorrelating multiuser detector; Performance analysis; Received signal stream; Signal-adapted criterion; Simulation results; Window length